Long chain branched impact copolymer of polypropylene: microstructure and rheology - Chikhalikar, Kalyani; Deshpande, Anushree; Pol, Harshawardhan; Dhoble, Deepa Arun; Jha, Saroj; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Lele, Ashish K. (Polymer Engineering and Science, 2015)
A biphasic impact copolymer of polypropylene (ICP) was modified with peroxide by reactive extrusion process resulting in reduced melt flow index, improved melt strength, and higher die swell. The polymers were for the first time subjected to systematic rheological and microstructural characterization in an effort to understand their structure-property relations. In shear rheological tests, the modified ICP displayed higher flow activation energy, reduced values of loss tangent and nearly equal frequency dependence of storage and loss modulli. The modified ICP also showed strain hardening behaviour in uniaxial extensional rheology and higher crystallization temperature in differential scanning calorimetry (DSC). All these are definitive indications of the presence of long chain branches (LCB). Fitting the rheological data of modified ICPs with the eXtended Pom Pom (XPP) model indicated the presence of LCB on the higher molecular weight fraction in the polymer, a result which was corroborated with multi-detector high temperature gel permeation chromatography (HT-GPC). More importantly, the matrix and rubber phases of the ICP were separately characterized for presence of long chain branching by rheology, DSC and HT-GPC. The results indicate that while LCB existed in the matrix phase, microgels were present in both phases indicating that the reaction with peroxide occurred in both phases. POLYM. ENG. SCI., 55:1463-1474, 2015. (c) 2014 Society of Plastics Engineers